Institutional Innovations for Climate Smart Agriculture: Assessment of Climate-Smart Village Approach in Nepal - Ghimire, Rajiv; Khatri-Chhetri, Arun; Chhetri, Netra (Frontiers in Sustainable Food Systems, 2022)
Institutions have a crucial role in communicating climate science into meaningful forms and to develop context specific adaptation options. Led by multiple institutions, Climate Smart Village (CSV) in Nepal is an organized approach to designing location specific package of interventions in response to climatic and other ongoing changes in the agricultural system. While addressing the impending risk of climate change and promoting food security objectives in smallholder settings, the CSV approach aims to increase the adoption of Climate Smart Agricultural (CSA) technologies at the local levels. One of the challenges, however, has been to sustain and scale the CSA technologies and practices. Based on the in-depth review of policy documents, field observations, and interviews with stakeholders involved in the implementation of pilot programs, this study evaluates the institutional framework of the CSV approach in the Gandaki region, Nepal. Our analysis proposes a revised conceptual model of innovation in the agricultural system that contributes to an increase in knowledge, attitude, and skills of multiple stakeholders for agricultural adaptation and the scaling of appropriate options. Our case demonstrates that while the scaling of the CSV approach is a concern, the institutional innovation around CSV has been instrumental in making farmers aware of CSA technologies. This has been done largely through collaboration among public, private, civil society organizations, and communities. This collaborative effort illustrates the possibilities for scaling the CSV approaches in the future and highlights their contribution to climate and development goals.